Barefoot global health diplomacy : field experiences in international relations, security, and epidemics - Kevany, Sebastian (Academic Press, 2021)
Barefoot Global Health Diplomacy: Field Experiences in International Relations, Security, and Public Health Epidemics fills real-world gaps in training for those destined to work on health and health systems in challenging, resource-deprived environments. Key topics include global health programs and individual adaptability for developing country settings, the interface between different actors in the global health diplomacy realm (e.g. ambassadors, embassies and the military), the ethical and economic implications of global health diplomacy at the service delivery level, the definition and illustration of the 'smart global health' paradigm, and the essential elements for individuals and organizations to design and deliver advances in international relations and altruism. This book provides an accessible, practical resource on advanced aspects of global health program design and delivery for global health practitioners and other international staff working on public health initiatives and programs in developing countries.